Involvement of matrix metalloproteinases in capillary degeneration following NMDA-induced neurotoxicity in the neonatal rat retina. (May 2019) - Asano, Daiki; Morita, Akane; Mori, Asami; Sakamoto, Kenji; Ishii, Kunio; Nakahara, Tsutomu
Abstract: Interactions between neuronal cells and vascular cells in the retina are critical for maintaining retinal tissue homeostasis. Impairment of cellular interactions contributes to development and progression of retinal diseases. Previous studies demonstrated that neuronal cell damage leads to capillary degeneration in an N -methyl-D-aspartic acid (NMDA)-induced retinal degeneration model. However, the mechanisms underlying this phenomenon are not fully understood. In this study, we examined the possible role of matrix metalloproteinase (MMP)-9 in neuronal cell loss and capillary degeneration in NMDA-treated retinas of neonatal rats. Intravitreal injection of NMDA (50 or 200 nmol) was performed on postnatal day (P) 7 and morphological changes in retinal neurons and vasculature were examined on P14. The MMP inhibitor CP101537 (100 nmol) or vehicle (dimethyl sulfoxide) was intravitreally injected simultaneously with, or 2 days after, NMDA injection. CP101537 protected against neurovascular degeneration in a time-dependent manner as follows: 1) simultaneous injection of CP101537 with NMDA prevented morphological changes in retinal neurons induced by NMDA (50 nmol); and 2) reduction in capillary density and number of vertical sprouts induced by NMDA (200 nmol) was prevented when CP101537 was injected 2 days after NMDA injection. Gelatin zymography and western blot analyses indicated that activity and protein levels of MMP-9 were enhanced from 4 h to 2 days after NMDA injection. Increased activity and protein levels of MMP-9 were suppressed by MMP inhibitors (CP101537 and GM6001). In situ zymography revealed that MMP activity was enhanced throughout the retinal vasculature in NMDA-treated retinas. These results indicate that MMP-9 plays an important role in neurovascular degeneration in the injured retina. Inhibition of MMP-9 may be an effective strategy for preventing and reducing neurovascular degeneration. Highlights: Excessive dose of NMDA induces retinal neurovascular degeneration. Neuronal cell loss precedes capillary degeneration following NMDA treatment. MMP inhibitors protect neuronal and vascular cells in NMDA-treated retinas. MMP-9 plays an important role in neurovascular degeneration in injured retinas. Inhibition of MMP-9 may be an effective strategy for neurovascular degeneration.